Substitution of Human Papillomavirus Type 16 L2 Neutralizing Epitopes Into L1 Surface Loops: The Effect on Virus-Like Particle Assembly and Immunogenicity - Chabeda, Aleyo; van Zyl, Albertha R.; Rybicki, Edward P.; Hitzeroth, Inga I. (Frontiers in Plant Science, 2019)
Cervical cancer caused by infection with Human papillomaviruses (HPVs) is the 4th most common cancer in women globally, with the burden mainly in developing countries due to limited healthcare resources. Current vaccines based on virus-like particles (VLPs) assembled from recombinant expression of the immunodominant L1 protein are highly effective in the prevention of cervical infection; however, these vaccines are expensive and type-specific. Therefore, there is a need for more broadly protective and affordable vaccines. The HPV-16 L2 peptide sequences 108-120, 65-81, 56-81 and 17-36 are highly conserved across several HPV types and have been shown to elicit cross-neutralising antibodies. To increase L2 immunogenicity, L1:L2 chimaeric VLPs (cVLP) vaccine candidates were developed. The 4 L2 peptides mentioned above were substituted into the DE loop of HPV-16 L1 at position 131 (SAC) or in the C-terminal region at position 431 (SAE) to generate HPV-16-derived L1:L2 chimaeras. All 8 chimaeras were transiently expressed in Nicotiana benthamiana via Agrobacterium tumefaciens-mediated DNA transfer. SAC chimaeras predominantly assembled into higher order structures (T=1 and T=7 VLPs), whereas SAE chimaeras assembled into capsomeres or formed aggregates. Four SAC and one SAE chimaeras were used in vaccination studies in mice, and their ability to generate cross-neutralising antibodies was analysed in HPV pseudovirion-based neutralisation assays. Of the 7 heterologous HPVs tested, cross-neutralisation with antisera specific to chimaeras was observed for HPV-11 (SAE 65-18), HPV-18 (SAC 108-120, SAC 65-81, SAC 56-81, SAE 65-81) and HPV-58 (SAC 108-120). Interestingly, only anti-SAE 65-81 antiserum showed neutralisation of homologous HPV-16, suggesting that the position of the L2 epitope display is critical for maintaining L1-specific neutralising epitopes.